(untitled) (Cadernos de Sociomuseologia, 2021)
This essay presents perspectives about the institutionalization of works by trans artists in museum collections. The contribution to this analysis comes from the Brazilian artists Élle de Bernardini (1991) and Lyz Parayzo (1994), who have works collected at the Art Museum of Rio (MAR), Niterói Contemporary Art Museum (MAC), Art Museum of Rio Grande do Sul (MARGS), Contemporary Art Museum of Rio Grande do Sul (MAC-RS), Santander Brasil Colection, Modern Art Museum in Rio de Janeiro (MAM-RJ), National Museum of the Cultural Complex of the Republic – Honestino Guimarães, Museum of Sexual Diversity, Italian Embassy in Brazil and Pinacoteca of the State of São Paulo. The main aim is to understand the process of musealization from the narrative construction of itself of each artist, the connection between those narratives and the agendas about gender and the artists’ conditions. As well, the text discusses the presence and absence of the agenda and the (re)exhibitions of the artworks. In this sense, the researcher has done an interview with two artists about trans visibility in museum collections. Keywords: Trans Narratives; Museums Collections; Élle de Bernardini; Lyz Parayzo;